A single mutation in chikungunya virus affects vector specificity and epidemic potential. - Konstantin A Tsetsarkin; Dana L Vanlandingham; Charles E McGee; Stephen Higgs (PLoS Pathogens, 2007)
Chikungunya virus (CHIKV) is an emerging arbovirus associated with several recent large-scale epidemics. The 2005-2006 epidemic on Reunion island that resulted in approximately 266,000 human cases was associated with a strain of CHIKV with a mutation in the envelope protein gene (E1-A226V). To test the hypothesis that this mutation in the epidemic CHIKV (strain LR2006 OPY1) might influence fitness for different vector species, viral infectivity, dissemination, and transmission of CHIKV were compared in Aedes albopictus, the species implicated in the epidemic, and the recognized vector Ae. aegypti. Using viral infectious clones of the Reunion strain and a West African strain of CHIKV, into which either the E1-226 A or V mutation was engineered, we demonstrated that the E1-A226V mutation was directly responsible for a significant increase in CHIKV infectivity for Ae. albopictus, and led to more efficient viral dissemination into mosquito secondary organs and transmission to suckling mice. This mutation caused a marginal decrease in CHIKV Ae. aegypti midgut infectivity, had no effect on viral dissemination, and was associated with a slight increase in transmission by Ae. aegypti to suckling mice in competition experiments. The effect of the E1-A226V mutation on cholesterol dependence of CHIKV was also analyzed, revealing an association between cholesterol dependence and increased fitness of CHIKV in Ae. albopictus. Our observation that a single amino acid substitution can influence vector specificity provides a plausible explanation of how this mutant virus caused an epidemic in a region lacking the typical vector. This has important implications with respect to how viruses may establish a transmission cycle when introduced into a new area. Due to the widespread distribution of Ae. albopictus, this mutation increases the potential for CHIKV to permanently extend its range into Europe and the Americas.